Efectos de la intensidad y oportunidad de raleo sobre la producción volumétrica de Grevillea robusta A. a los 20 años en el sur de Misiones, Argentina - Keller, Aldo Esteban (2019)
The objective of this work was to analyze an experiment of thinning modalities with Grevillea robusta A. installed in complete random blocks with 2 levels of intensity and witnesses and 3 levels of opportunity in 3 repetitions. The intensity treatments were defined by the basal area, and characterized in: without thinning (witness) and 20 and 40 % thinning of basal area. The 3 opportunity treatments were defined with thinning at 2, 4 and 6 years’ intervals. There were no statistically significant differences in total volume production between treatments at 20 years, consequence of the application of different intensities of thinning.